Phase equilibrium constraints on conditions of granulite facies metamorphism at Scourie, NW Scotland - Johnson, Tim; White, R. (Geological Society Publishing House, 2011)
The metamorphic evolution of a metapyroxenite and metagabbro from Scourie, NW Scotland, is investigated using phase equilibria modelled in the NCFMASHTO (Na2O–CaO–FeO–MgO–Al2O3–SiO2–H2O–TiO2–O) system. The calculated stability fields for the observed assemblages in each rock overlap and imply conditions of 8.5–11.5 kbar and 875–975 °C for the peak of granulite-facies (Badcallian) metamorphism. The lack of any evidence for the former presence of garnet in the metapyroxenite suggests that the rocks cannot have reached pressures much in excess of those recorded at the metamorphic peak. The growth of coronas of plagioclase, orthopyroxene and magnetite replacing garnet in the metagabbro is consistent with near-isothermal retrograde decompression from the metamorphic peak to pressures of 7–9 kbar. The constraints on the pressure–temperature evolution imposed by the modelled phase equilibria are more consistent with a process of crustal growth dominated by magmatic accretion rather than by significant tectonic thickening during the early Scourian.